Pengaruh Tax Planning, Corporate Governance dan Deffered Tax Expenses Terhadap Earning Management Pada Perusahaan Properti dan Real Estate yang Tercatat di BEI Tahun 2013-2017 - Marifatul Afifah (Faculty of Economics and Business, University of Pancasakti Tegal, 2018)
The research objectives are 1). To know the effect of tax planning, corporate governance and deffered tax expenses simultaneously to earning management. 2). To know the effect of tax planning on earning management. 3) Is there any influence of corporate governance on earning management. 4). Is there any effect of deffered tax expenses on earning management. This type of research is quantitative with descriptive approach. Data collection method used in this research is documentation method. While the technique of data analysis and Hypothesis Testing using classical assumption testing, multiple regression analysis, partial test, simultaneous test, and Coefficient of Determination. The research results prove that there is influence of tax planning, corporate governance and deffered tax expenses simultaneously to earnings management evidenced from result of simultaneous test test obtained probability sig value equal to 0,001 smaller than value a that is equal to 0,05. The effect of tax planning on earning management is evidenced from the partial tax planning results on earning management obtained probability sig value of 0.012 which is smaller than a value of 0.05. There is influence of corporate governance to earnings management evidenced from result of partial examination of corporate governance to earnings management got probability sig value equal to 0,002 smaller than value a that is equal to 0,05. There is no effect of deffered tax expenses on earning management evidenced from the partial test results deffered tax expenses to earnings management probability obtained sig value of 0.859 greater than the value of a is 0.05.